KONDISI SOSIAL EKONOMI KELUARGA TENAGA KERJA INDONESIA (TKI) DI DESA SICINI KECAMATAN PARIGI KABUPATEN GOWA (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2021)
This journal aims to find out how the socio-economic conditions This thesis aims to 1) determine the socio-economic conditions of the families of Indonesian workers (TKI) in Sicini Village, Parigi District, Gowa Regency, 2) describe the factors that influence people to become Indonesian Workers (TKI) in Sicini Village, Parigi District, Gowa Regency. The results showed that the socio-economic conditions of the TKI family in Sicini Village, Parigi District, Gowa Regency. The general profession of the community is only as a rice farmer, generally, the job can only be done once a year due to weather factors, the yield is not small or the income is low. So that requires people to find other jobs. After becoming Indonesian Migrant Workers (TKI) in Malaysia, the economic conditions of the migrant workers' families in Sicini Village, Parigi District, Gowa Regency have changed significantly, they can have more income to meet their daily needs. TKI families, especially children, can continue their education to the university level because the income of their parents who work as migrant workers is quite large so that they are able to pay for educational needs and are also able to make long-term investments such as building houses, buying vehicles, rice fields and others. There are several factors that cause people to choose to become migrant workers, namely, driving factors, pull factors, obstacle factors, and personal factors. However, the main factor that causes people to become migrant workers is the economy. They also want to live independently and not depend on other people and solely on the future of their family.